Boston, Sunday, January 12, 1777 : the letters, whereof the following are extracts, being wrote by several field officers in the American army, arrived in town last evening, and are made public for the perusal of the several gentlemen who subscribed to defray the expences of obtaining intelligence from the army (Printed by Powars and Willis., 1777)
Extracts of six letters from various field officers from Pennsylvania and New Jersey describing the battle of Trenton; dated Dec. 24, 1776, to Jan. 2, 1777, which arrived in Boston and made available for those who subscribed to defray the expense of obtaining intelligence from the Army.